(untitled) (Research, Society and Development, 2021)
The present work had as its theme the sustainability practices from a Bourdius perspective. The methodology adopted in the formulation of this work was based on bibliographical research, through consultations in books, magazines, search of manuals, treatises, articles published on the internet. Bibliographic research seeks to explain and discuss a topic based on theoretical references published in books, magazines, periodicals and others. Thus, the general objective seeks to analyze how the organization of sustainable development takes place based on the reality of riverside dwellers in the Amazon region. The specific objectives seek to describe the Bourdiusian view on sustainability, define what sustainable development is and its presence in society, present the familiar agricultural practice of riverside people in the Amazon available in the literature and finally, understand, from a case study, the practice of sustainable development by riverside dwellers in the Amazon region in their agricultural practices. The results indicate that sustainable family farming has contributed in a unique way to the development of local economies, especially in municipalities with large productive demands and that see family farming as a source of income for the movement of their economic activities. Finally, the present work leaves the subject open, proposing that in the future a new research be carried out in order to contextualize the subjects and field study presented here, continuing the approached subject.